Revisão sistemática e meta-análise das técnicas de manejo de aves usadas em aeródromos - Portela, Diana Guimarães (2022)
Aeronautical accidents caused by collisions with birds have grown dramatically in recent decades. The damage caused by this type of accident goes beyond the economic loss with the maintenance of the aircraft, since the ecological consequences are equally significant, such as collisions always resulting in the death of the birds involved. Faced with this situation, aerodrome managers adopt bird management techniques in order to keep the birds away from the airport environment. Therefore, this study aims to evaluate the effectiveness of the main bird management techniques, in addition to presenting a detailed systematic review on the techniques used. A total of 23 papers was selected for the systematic review and 14 of them presented the necessary data for the meta-analysis. The results obtained show that the control of grass height is the most applied technique in airfields, however, the meta-analysis indicates that falconry is the most effective method to bird scattering. Despite that no technique alone can completely eliminate the risk of collisions between birds and aircrafts, their use associated with knowledge of the habits of the target species significantly reduces the risk of accidents. It is also necessary to make a greater effort to develop studies with better methodological robustness and clarity in the data to properly assist in decision making by aerodrome operators